ΑΘΗΝΑ ΨΑΡΟΠΟΥΛΟΥ, "Σαν μια νεάνις που φορεί πλατύ φουστάνι": Η εμπειρίκεια επιφάνεια ως σύνθεση μνήμης και φωτογραφίας - Ψαροπούλου Αθηνά (Σύγκριση/Comparaison/Comparison, 2022)
“Like a young woman in a loose-fitting dress”: The epiphany of Andreas Embiricos as fusion of memory and photography This paper attempts to shed light on the significance and role of the four “epiphanies of the past recaptured”, which are an integral part of the “analysis” of the poem “8th January 1942” by Andreas Embiricos and derive from the verbal image of the verse “Like a young woman in a loose-fitting dress”. In these epiphanies, time becomes fluctuant and the memory of the past (specifically the memory of four exceptional women-muses of important surrealist creators) is fused with the present experience of the poet. The fourth of them, which embodies Embiricos’ first wife, enlivens the memory of a past event and a photograph. Those two turn into a present reality, in a complete osmosis of the epiphanic object’s unconscious, revealed through the photograph, with the epiphanic subject’s unconscious that perceives it. In effect, spatial time blends with psychological time, as in communicating vessels, revealing the “convulsive beauty” of surreality.